Breaking Down Barriers: Improving Access to Quality Endometriosis Care - Nieto Rey, Nathalia; Lopez I, Jorge D.; Quintero M, Angélica M.; Sanabria P, Luis F.; Villegas-Echeverri, Juan Diego (Seminars in Reproductive Medicine, 2025)
Endometriosis affects an estimated 200 million women globally, yet significant barriers hinder access to timely and appropriate care. These barriers encompass various aspects, including societal normalization of menstrual pain, leading to delayed diagnosis and misinterpretation of symptoms as “normal” period pain. This normalization, coupled with the stigma surrounding menstrual health, often results in the dismissal of symptoms by both individuals and healthcare providers. Furthermore, access is often limited by socioeconomic factors and healthcare disparities, making specialized treatments financially prohibitive for many. There is an urgent need for a multi-pronged approach to improve access to quality endometriosis care. This includes increased education and awareness for patients, healthcare providers, and the public to destigmatize the condition and promote early recognition of symptoms. Additionally, addressing healthcare system reforms and socioeconomic disparities is essential to ensuring equitable access to effective diagnostic tools and treatment options for all affected individuals. Further research is crucial to better understand the underlying mechanisms of the disease, improve diagnostic tools, and develop more effective treatments.
Keywords: endometriosis; burden; barriers; quality of life; chronic pelvic pain